Metagenomics: An Approach for Unraveling the Community Structure and Functional Potential of Activated Sludge of a Common Effluent Treatment Plant - Vasudeva, Gunjan; Singh, Harpreet; Paliwal, Sakshi; Pinnaka, Anil Kumar (Frontiers in Microbiology, 2022)
The common effluent treatment plant located at Baddi treats the industrial effluent from varieties of industries, leading to the pooling of a diverse range of substrates and metabolites. The nutrient loading and its availability decide the balance of the microbial community and its diversity. The samples thus collected from the activated sludge (BS14) of CETP and Sirsa river (SR1) from the vicinity of CETP effluent discharge were processed for the whole metagenome analysis to reveal the microbial community and its functional potential. The taxonomic classification of the BS14 sample showed the dominance of the bacterial community with 96% of abundance, whereas the SR1 was populated by eukaryotes representing 50.4% of the community of SR1. The bacterial community of SR1 was constituted of 47.2%. The functional analysis of BS14 and SR1 with GhostKOALA against the KEGG database assigned 43.7% and 27.8% of the ORFs with functions. It revealed the xenobiotic degradation modules with complete pathways along with resistance against the beta-lactams. The analysis with the Comprehensive antibiotic resistance database (CARD) revealed 33 and 32 unique types of antimicrobial resistance in BS14 and SR1, respectively. Both the samples were dominated by the beta-lactam resistance genes. The Carbohydrate Active enzymes (CAZy) database assigned a total of 6611 and 2941 active enzymes to BS14 and SR1, respectively. In contrast, the Glycosyl Hydrolases (GH) and Glycosal Transferases (GT) class of enzyme were found to be abundant in both the samples as compared to Polysaccharide Lyases (PL), Auxillary Activities (AA), Carbohydrate Esterases (CE), and Carbohydrate-Binding Module (CBM).